Contribution of frustules and mucilage trails to the mobility of diatom Navicula sp - Chen, Lei; Weng, Ding; Du, Chuan; Wang, Jiadao; Cao, Shan (Scientific reports, 2019)
The secreted mucilage trails of the diatom Navicula sp. in the process of motility were studied by scanning electron microscopy (SEM), transmission electron microscope (TEM), atomic force microscopy (AFM) and Raman spectra etc. Contrary to previous studies, force measurement was taken directly on the mucilage trails of live cells using the method of in situ force mapping by AFM. The retraction force curve presented an increased tip-substrate peak and a small saw-tooth pattern tip-mucilage peak. Especially, same measurements on various substrates with different surface energy revealed that the mucilage trails actually functioned as a medium increasing the adhesive force between the diatom and substrates, which is crucial to diatom’s adhesion and locomotion. In addition, the mechanical properties of mucilage trails were quite different from mucilage strands in the maximum adhesive force and the maximum polymer extension length. Raman spectra indicated the difference in compositions that both of the two kinds of mucilages had proteins and polysaccharide, but the mucilage strands contained some other components with C=O, —CH 2 — and —CH 3 asymmetric and symmetric stretches. This research hammers out more precise information about mucilage trails which would be useful in terms of diatom motility and biofouling prevention.